Determining the band-structure of an InGaNAs/GaAs semiconductor laser structure using non-destructive photomodulated reflectance measurements and k·p studies - Choulis, Stelios A.; Tomić, Stanko S.; O'Reilly, Eoin P O (My University, 2003)
We describe micro-photomodulated reflectance (PR) measurements on a representative dilute-N InGaNAs/GaAs-based laser device structure designed to emit at 1.3 μm. The quantum well (QW) transition energies obtained from PR are modeled using a realistic 10-band k·p Hamiltonian that includes tight-binding-based energies and coupling parameters for the N-levels. From this we are able to determine accurately the band structure and thus predict some important device properties for this InGaNAs/GaAs-based laser device
Keywords: Semiconductors; Modulation spectroscopy; Semiconductor lasers; Binding energy